Problems of special education services for believers in Malang City - Lestari Eko Wahyudi; Bambang Supriyono; Suhartono Winoto (Inovasi Kurikulum)
Over seven years, policy implementation faced challenges, including suboptimal synergy among involved parties, administrative confusion in education, and discrimination against non-religious groups by regional authorities. These challenges perpetuate negative stereotypes and hinder inclusive education access for believers. This research is then directed to analyze the collaborative governance model as a solution to unravel problems that occur in implementing educational services in faith groups. The collaborative governance model aims to elaborate and map the involvement and role of each actor to support the smooth implementation of policies. The principles carried out in it are deliberative, holistic, constructive, and formal, applicable as the basis for implementing inclusive policies. The Soft Systems Methodology (SSM) analysis reveals issues in fulfilling special education services (trust) at the Malang City Education and Culture Office. Problems include partial services, a conservative service acquisition model, and insufficient human resource competence. These findings underscore the need for systemic interventions to ensure inclusive and efficient service delivery.